(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, an attempt has been made to dwell on the social and economic life of Indian citizens living in Turkestan in the late 19th and early 20th centuries. Attempts were made to use mainly the documents of the court of the Governor-General of Turkestan and the relevant information of historians. The periodic boundaries of the case can be traced back to the end of the 19th and the beginning of the 20th centuries, when the information on the subject was mainly stored in the documents of the court of the Governor-General of Turkestan. Most of this information is currently stored in the funds of the Central State Archive of the Republic of Uzbekistan. An attempt was also made in the coverage of the case to briefly dwell on the entry of Indian nationals and the appearance of their first settlements. In the main part of the work, an attempt has been made to dwell on the restrictions imposed by the Turkestan and Colonial Administration on Indian citizens living in Turkestan during this period and the impact of these restrictions on Indian citizens in the region.